Non-Revenue Water And Efficiency Of States’ Water Supply Management In Malaysia - Nariman Mohd Saad; Madya Abdul Rahim Anuar (International Journal of Supply Chain Management, 2019)
Non-Revenue Water (NRW) is currently being one of the issues heatedly discussed in Malaysia and reflects the performance of the states’ water supply management. In 2008, the Federal Government restructures the water industry and centralized the water management of the state government by establishing SPAN (National Water Services Commission) and PAAB (Water Asset Management Company). The objective of SPAN and PAAB is to improve the efficiency of states’ water operators in Peninsular Malaysia including Labuan. The Government has urged the state water supply to manage NRW problems more effectively because it gives an impact on the efficiency as a whole, thus the revenue collection specifically. Therefore, this study is to measure the effect of NRW on the efficiency of the state water supply agencies following the restructuring of the water industry in Malaysia. DEA approach (Data Envelopment Analysis) has been used to measure the technical efficiency and second stage regression (Tobit) is used to determined factors that effect efficiency. The findings showed that immediate strategies need to be taken to improve efficiency and NRW of the states’ water supply management. Keywords— Non Revenue Water, DEA, SPAN, PAAB, Malaysia